The Effect of Guessing Word Game in Students’ Reading Comprehension Achievement - Aprillyani Ginting; Sri Minda Murni (Universitas Negeri Medan, 2013)
This study deals with The Effect of Using Guessing Word GameTechnique on Students’ Achievement in Reading Comprehension. Theobjective of the study is to find out whether Guessing Word GameTechnique significantly affects students’ achievement in readingcomprehension. The population of the study is the second year students of2011/2012 of SMPN 28 Medan, where there are seven parallel classes withtotally 280 students and the sample which is chosen randomly are twoclasses (40 studends). The sample is divided into two groups, experimentalgroup taught by using Guessing Word Game Technique and control grouptaught by using conventional technique. The data were obtained by usingmultiple choice and analyzed by using t-test formula. The result of theresearch shows that t-observed (1.77) is higher than t-table (1.667) on df 78and the level of significance 0.05. It means that there is a significant effectof using Guessing Word Game Technique in students’ readingcomprehension achievement or in another words the hypothesis is accepted.